Ambient electrohydrogenation of N2 for NH3 synthesis on non-metal boron phosphide nanoparticles: the critical role of P in boosting the catalytic activity. Issue 27 (1st July 2019) - Zhu, Xiaojuan; Wu, Tongwei; Ji, Lei; Li, Chengbo; Wang, Ting; Wen, Shaohua; Gao, Shuyan; Shi, Xifeng; Luo, Yonglan; Peng, Qiling; Sun, Xuping
Abstract : As a non-metal electrocatalyst for the N2 reduction reaction, boron phosphide nanoparticles offer a high NH3 yield of 26.42 μg h −1 mgcat. −1 and a high faradaic efficiency of 12.7% at –0.60 V vs. the reversible hydrogen electrode in 0.1 M HCl. Abstract : As a carbon-neutral alternative to the Haber–Bosch process, electrochemical N2 reduction enables environment-friendly NH3 synthesis under ambient conditions but needs active electrocatalysts for the N2 reduction reaction (NRR). In this communication, we report on the first experimental demonstration that non-metal boron phosphide (BP) nanoparticles can be used as a high-efficiency catalyst for the ambient electrohydrogenation of N2 to NH3 with excellent selectivity. In 0.1 M HCl, this catalyst offers a high NH3 yield of 26.42 μg h −1 mgcat. −1 and a high faradaic efficiency of 12.7% at −0.60 V vs. the reversible hydrogen electrode, much superior to those of reported B catalysts. Such an enhancement is attributed to the fact that P in BP further weakens the NN bond while simultaneously strengthening the B–N bond and favors the exposure of more active sites for the NRR catalysis, which is supported by density functional theory calculations.